Gender-role portrayals in children's television advertisements - Félix Neto (2005)
Using content analysis, gender role stereotyping in Portuguese television commercials aimed at children was examined. The goals of the study were to: (1) provide current data on level and content of gender stereotyping in Portugal; (2) compare levels of stereotyping in three countries, namely Portugal, the USA and Great Britain. One hundred and twenty two commercials were content analysed by two raters, one male and the other female, to check reliability. The advertised products covered by this analysis included toys, food, mass media communication equipment and others. Each advertisement was coded according to twelve criteria including the ethnicity and gender of the people appearing, gender of central figure and of any "voice-over" in the commercial, presence or absence of music, other sales-related content, activity, aggression and loudness. The results concerning gender-role were equivocal. Six of the nine analyses revealed significant differences among advertisements recorded in Portugal, United States and Britain. The implication for the regulation of advertisements to children is discussed. © 2005 A B Academic Publishers.